Amarcord - Rota, Nino 1911-1979 (<<The>> Criterion collection, 2006)
"In this movie Fellini portrays his home town of Rimini as he remembered it in the 1930's, during his young days. Many bizarre but very warm and human characters and specific Mediterranean humor made this movie the most popular of all Fellini's works" [Internet Movie Database]
Bildformat 1.85:1, enhanced for 16:9 widescreen TVs. - New restored high-definition digital transfer
Orig.: Italien, Frankreich 1973
Enth. audio commentary by film scholars Peter Brunette and Frank Burke ; deleted scene ; new, 45-minute documentary "Fellini's homecoming", on the complicated relationship between the celebrated director, his hometown and his past ; video interview with star Magali Noël ; Fellini's drawings of characters in the film ; "Felliniana", a presentation of ephemera devoted to "Amarcord", from the collection of Don Young ; audio interviews with Fellini, his friends, and family by Gideon Bachmann
Keywords: Fellini, Federico -- Childhood and youth -- Drama; Alltag, Brauchtum; Stadt; Cities and towns -- Italy -- Drama; Italien; Italy -- Social life and customs -- 1914-1945 -- Drama; Rimini (Italy) -- Drama; Fiktionale Darstellung; Comedy films; Foreign films